Remote System for Oil Spill Detection Based on ZigBee and GIS - Hou, Huishu; Zhang, Guojun (International Journal of Online and Biomedical Engineering (iJOE), 2016)
In order to solve the problem of long delay time and low data precision, a remote system for oil spill detection based on ZigBee and GIS is designed in this paper. This paper analytically summarizes the results obtained from surveying spectral characteristics of spill oil film at sea. M along use of AVHRR and TM data, the image of oil spill in several marine accidents has been processed and identified, and the place and area of oil spill in obtaining images are the same as investigation in the scene of accidents. Simulation results show that the proposed system which bases on the ZigBee and GIS can thus improve overall system performance substantially.